Human Papillomavirus 16 L2 Recruits both Retromer and Retriever Complexes during Retrograde Trafficking of the Viral Genome to the Cell Nucleus - Pim, David (J Virol, 2021)
Previous studies have identified an interaction between the human papillomavirus (HPV) L2 minor capsid protein and sorting nexins 17 and 27 (SNX17 and SNX27) during virus infection. Further studies show the involvement of both retromer and retriever complexes in this process since knockdown of proteins from either complex impairs infection. In this study, we show that HPV L2 and 5-ethynyl-2′-deoxyuridine (EdU)-labeled pseudovirions colocalize with both retromer and retriever, with components of each complex being bound by L2 during infection. We also show that both sorting nexins may interact with either of the recycling complexes but that the interaction between SNX17 and HPV16 L2 is not responsible for retriever recruitment during infection, instead being required for retromer recruitment. Furthermore, we show that retriever recruitment most likely involves a direct interaction between L2 and the C16orf62 subunit of the retriever, in a manner similar to that of its interaction with the VPS35 subunit of retromer. IMPORTANCE Previous studies identified sorting nexins 17 and 27, as well as the retromer complex, as playing a role in HPV infection. This study shows that the newly identified retriever complex also plays an important role and begins to shed light on how both sorting nexins contribute to retromer and retriever recruitment during the infection process.